Correlation between gonial angle and dynamic tongue collapse in children with snoring/sleep disordered breathing – an exploratory pilot study - S. Anderson; N. Alsufyani; A. Isaac; M. Gazzaz; H. El-Hakim (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Drug induced sleep endoscopy (DISE) is hoped to identify reasons of failure of adenotonsillectomy (AT) in treating pediatric sleep disordered breathing (SDB). Maxillomandibular disproportion has been studied as another association which may explain alternative pathogenesis of SDB. We aimed to explore the relation between the size of the gonial angle and inclination of the epiglottis measured from cone beam CT (CBCT) and tongue base collapse based on DISE in children with SDB. Method A retrospective chart review was conducted at a tertiary pediatric center. Children (6-17 years old) assessed at a multi-disciplinary Upper Airway Clinic, diagnosed with SDB and maxillo-mandibular disproportion (MMD), and who underwent DISE were eligible. Variables obtained from the electronic medical records of the clinic and prospective database included demographics, comorbidities, surgeries performed, investigations, DISE findings and CBCT findings. The gonial angle of subjects with and without tongue base collapse (TBC) on SNP were compared. Results In total 29 patients (13 male, 8 female) age 6-17 (median= 9) were eligible for the study from January 2009 – July 2016. We included 11 subjects, and 10 comparators. The mean gonial angle of the TBC group was 139.3°± 7.6°, while that of the comparison group was 129.4°±3.5 (mean difference -9.937, 95% CI of -15.454 to - 4.421, P = 0.001, power of test 0.95). Additionally, the mean inclination of the epiglottis had a mild positive correlation (r=0.32, p<0.05) with the gonial angle, in the whole cohort. Conclusions This pilot study suggests that TBC may be mediated by a wider gonial angle in children with SDB patients. The posterior tilt of the epiglottis on CBCT may be a surrogate sign of TBC.